Out-of-School Exposure to English in EFL Teenage Learners: Is It Related to Academic Performance? - Linh Tran; Imma Miralpeix (MDPI AG, 2024)
Learning a Foreign Language (FL) beyond the classroom has become common practice thanks to advances in technology and the use of English as a Lingua Franca. This study explores the types and amount of out-of-school informal exposure to English that Spanish secondary school students typically receive in their daily lives. Informed by recent literature on the influence of extramural activities on FL proficiency, the second aim of this study is to investigate the potential relationship between out-of-school exposure and academic performance, as measured by English school grades. Data were obtained from a questionnaire answered by secondary school students aged 12-16 (N = 2015) regarding the different types and amounts of activities they perform in English outside school. Findings revealed that teenage learners were most frequently exposed to English through audiovisual input. Social media interaction, along with reading and writing (with or without digital support), were closely associated with their English marks. Other popular activities, such as listening to music or playing video games, were not found to be related to proficiency or even showed a negative correlation with it, while less popular activities, such as watching subtitled movies and series, could have greater potential for language learning. This study contributes to the understanding of informal practices in FL learning settings and provides insights that can help bridge interactive language practices and formal curriculum to create holistic learning experiences for language learners.